Online and offline clothing shopping behavior of selected consumers - Blancaflor, Sarah M. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This study aimed to identify the clothing shopping behavior of consumers. It aimed to point out changes brought about by awareness of online shopping such as: changes in frequency of shopping, changes in quantity of items bought, and changes amount spent on clothing as well as changes in the kinds of clothing items bought. The study also aimed to point out and compare consumer clothing shopping preferences both online and offline. Data was gathered through a survey questionnaire disseminated to random participants online and analyzed qualitatively. Results show a marked change in the frequency of browsing for clothing products and slight changes in frequency of shopping for clothing, quantity of clothing items bought, and amount spent on clothing.The findings of the research also show similarities between online and offline shopping habits in terms of payment, product comparison, and awareness of retailers' policies, terms, and conditions. The researcher concluded that it may take time for more significant changes in consumer behavior to take effect as online shopping is a relatively new phenomenon in the Philippines. Shopping online shows a lot of promise since a lot of consumers are already browsing clothing items online. Retailers need to make a conscious effort to address the needs and concerns of customers in order to encourage them to make purchases online. Consumers on the other hand need to be better acquainted with their shopping options. They should familiarize themselves more with online shopping especially with the online retailer's store policies, terms, and conditions. Knowing such things, the consumer will be able to make informed choices when they finally make an online purchase.